Gaming Disorder: The role of a gamers flow profile - Trent Footitt; Natasha Christofi; Dylan R Poulus; Michelle Colder Carras; Vasileios Stavropoulos (Addictive Behaviors Reports, 2024)
Digital games are widely popular and integral to contemporary entertainment. Nevertheless, a proportion of users present with disordered/excessive gaming behaviours, provisionally classified as Internet Gaming Disorder (IGD). Previous literature suggests examining the contribution of an individual’s profile of immersive engagement with their gaming activity, known as online flow, for disordered gaming behaviours. Therefore, the main goals of this study were (1) to categorise gamers into distinct profiles based on their online flow experiences and (2) to investigate the differences in disordered gaming among these different flow profiles. A sample of 565 gamers (12–68 years, Mage = 29.3 years) was assessed twice over six months with the Online Flow Questionnaire (OFQ), the Internet Gaming Disorder Scale-Short-Form (IGDS9-SF), and the Gaming Disorder Test (GDT). Latent profile analysis (LPA) identified five distinct profiles encompassing ’High-Flow with High Loss of Control’ (HF-HLOC; 14.0 %), ’Low Flow with Low Enjoyment’ (LF-LE; 11.9 %), ’Average Flow with Low Enjoyment’ (AF-LE; 17.5 %), ’Low Flow with High Enjoyment’ (LF-HE; 20.2 %), and ’High Loss of Sense of Time with Low Loss of Control’ groups (HLOT-LLOC; 36.5 %). As hypothesised, individuals across varying profiles evidenced differences in their concurrent and longitudinal disordered gaming behaviours. Overall, findings suggest that ’loss of sense of time’ may be the most pivotal factor in differentiating flow states and profiles during gaming, advocating its consideration in disordered gaming assessment and treatment.